Gallium Polymorphs: Phase‐Dependent Plasmonics. Issue 13 (2nd May 2019) - Gutiérrez, Yael; Losurdo, Maria; García‐Fernández, Pablo; Sainz de la Maza, Marta; González, Francisco; Brown, April S.; Everitt, Henry O.; Junquera, Javier; Moreno, Fernando
Abstract: Interest in gallium (Ga) is growing rapidly, thanks in part to its wide spectral tunability and its intriguing temperature‐dependent polymorphism. In order to exploit and control phase‐change plasmonics in the liquid and solid phases of Ga, an accurate understanding of the dielectric functions for each Ga phase is needed. A comprehensive analysis of the interdependence of the crystal structure, band structure, and dielectric function of the several Ga phases (liquid, α, β, γ, δ) is presented, showing that the selective presence of flat bands in the vicinity of the Fermi energy is crucial to understand the metallicity of each phase. The dielectric function obtained through first principles calculations is compared with experimental measurements obtained by spectroscopic ellipsometry. Cooling liquid Ga always produces a mixture of phases, and how the volume fraction of each phase may be deduced from these pure phase dielectric functions and an analysis of the measured spectra using a Bruggeman effective medium approximation is demonstrated. Figures of merit are presented, and applications of Ga polymorphism are discussed for propagating and localized surface plasmon resonances in Ga thin films and nanostructures, respectively. This research can have important implications on the phase change control for plasmonics/photonic applications with gallium. Abstract : Gallium (Ga) presents a wide temperature‐dependent polymorphism . In order to exploit and control phase‐change plasmonics in the liquid and solid phases of Ga, an accurate understanding of the dielectric functions for each Ga phase is needed. The authors report the first detailed analysis of the optical properties of the different α‐, β‐, γ‐ and δ‐Ga phases and its correlation with their crystalline and electronic structures.